Performance and emission characteristics of a direct injection diesel vehicle with different blends of CME biodiesel - Laguitao, Jeffrey James C. (2009)
Increasing public awareness on global warming and environmentalism coupled with the renowned oil crisis has brought about different developments around the world to utilize sustainable and environmental friendly alternative fuels. With the Philippines being the largest coconut exporter in the world, government and private sectors have tapped the potential of producing biodiesel from coconut oil. The most common method of production is the transesterification process which results to coco-methyl ester or CME. Current government regulations now mandate a 2% blend of biodiesel for all the commercial diesel being sold at the pumps. While there have been numerous laboratory studies of different kinds of biodiesel in different countries, there is none yet in the Philippines for the CME specifically in vehicles use. This study investigated the performance and emissions characteristics of a direct injection diesel vehicle using different blends of CME biodiesel inside a chassis dynamometer laboratory in the Philippines. The vehicles was driven at a standard Japanese driving cycle while measuring fuel consumption and emissions. A steady state test in road load simulation at three different speeds was also carried out as well as a maximum power test. Test results showed that fuel consumption improved by as much as 2.06% with the D99-B1 blend while the improvement gradually reduced as the amount of CME was increased. The fuel consumption starts to worsen at the blend of D50-B50 while the worst fuel consumption was observed with the pure CME at 11.13% decline from neat diesel fuel. Maximum power slightly improved with closely similar values from 1% to 10% CME blend with the D90-B10 fuel having the highest increase at +2.85% over neat diesel. Power reduction starts at D50-B50 again with pure CME having the biggest reduction with maximum power at 4.86% decline. Emissions test results showed that CME was able to decrease THC emissions by 41.23% with D97-B3 and CO emissions by 10.03% with D50-B50 compared to neat fuel. Oxides of nitrogen were also continuously decreasing as the blend of CME goes higher with the B100 CME having a reduction of 9.49% over neat diesel fuel. Steady state tests showed that effects of CME was not as evident compared to the transient drive cycle test.
"November 2009."
Vita.
Thesis (M.S. Mechanical Engineering)--University of the Philippines Diliman.
Keywords: Biodiesel fuels -- Philippines; Coconut oil -- Philippines; Diesel motor